ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL CERITA PADA MATERI ARITMATIKA SOSIAL - Justin Eduardo Simarmata (Jurnal Pendidikan Matematika Undiksha, 2022)
This research aims to determine the difficulties of students in solving story problems on social arithmetic material for class VII Junior High School. The method used in this research is the descriptive qualitative method. The research subjects were students of class VII D State Junior High School 1 West Malakat. There are three kinds of students’ ability in this research, namely: low, medium, and high. Data collection techniques used are test, interview, and documentation. The instruments in this study were test questions and interview guidelines. Data analysis techniques in this research are data reduction, data presentation, and conclusion. Based on the research analysis, there are three conclusions, namely: 1) the student who has high score has been able to understand the concept well but the student still found difficulties on applying principles and verbal problems, 2) the student who has medium score has been able to understand the concept, but the student still found difficulties on applying principles and verbal problems, and 3) the student who has low score has not been able to understand the concept and apply the principles and also found difficulties on answering verbal problems.